HUBUNGAN ANTARA KECERDASAN SPIRITUAL IBU, SOSIALISASI MORAL, INTERAKSI IBU-ANAK, DAN KARAKTER TEKUN ANAK USIA SEKOLAH PADA KELUARGA DI SLUM AREA. - Alfiasari Alfiasari (Balai Besar Litbang Pelayanan Kesejahteraan Sosial, 2018)
The persistent character formed is inseparable from the parents factor, such as mother's spiritual intelligence, moral socialization, and mother-child interaction. The objectives of this research are to: (1) identify and analyze the relationship between family and child characteristics, mother’s spiritual intelligence, moral socialization, and mother-child interaction with children's persistent character in urban slum area. This study used cross-sectional study design and purposive location selection. Respondents of this study included 44 mothers and 44 children aged 8-12 years who attend formal school, and live in slums in one area of North Jakarta. The average achievement of the mother's spiritual intelligence, moral socialization, and mother-child interaction, and the persistent character of the children based on the index are categorized as good enough. The results of the correlation test indicate that large of family, mother’s spiritual intelligence, moral socialization, and mother-child interaction had positively correlation with the persistent character of school age children. A significant positive relationship also occurs between spiritual intelligence and moral socialization. The mother-child interaction with moral socialization and mother’s spiritual intelligence also showed a very significant relationship.